Answer: y=(x/4)-(7/4)
Explanation:
The easiest way to solve for an inverse is to switch the x and y variables. For F(x)=4x+7, which is essentially equal to y=4x+7, you switch the x and y variables and get x=4y+7. You then solve for the y variable, as shown below, to obtain the inverse of the equation.
x=4y+7
4y=x-7
y=(x/4)-(7/4)
Answer:
(x) =
Let y = f(x) and rearrange making x the subject, that is
y = 4x + 7 ( subtract 7 from both sides )
y - 7 = 4x ( divide both sides by 4 )
= x
Change y back into terms of x, hence
5.2m questions
6.7m answers